Beyond Racial Capitalism Co-Operatives in the African Diaspora - Hossein, Caroline Shenaz (Oxford University Press, Incorporated, 2023)
Knowledge-making in the field of alternative economies has limited the inclusion of Black and racialized people's experience. This book aims to close that gap in development through a detailed analysis of cases in about a dozen countries where Black people live and turn to co-operatives to manage systemic exclusion